Tailoring electroactive poly(vinylidene fluorideco-trifluoroethylene) microspheres by a nanoprecipitation method - Macedo, A. S. (2020)
Poly(vinylidene fluorideco-trifluoroethylene) (P(VDF-TrFE)) microspheres were obtained by a nanoprecipitation method based on the deposition of a polymeric solution over a non-solvent (NS) solution. The effect of several parameters on sphere formation was evaluated, including copolymer concentration, NS content (methanol/water ratio) and surfactant type. Morphological and physico-chemical characterizations were performed. Depending on processing conditions, spheres with diameters ranging from ~100 to 1100nm with similar physico-chemical properties were obtained. Independently of the processing conditions, P(VDF-TrFE) microspheres crystallize in the electroactive phase with an average crystallinity of 26%. Thus, samples show the required characteristics for biomedical applications.